VD_FINDINFO HC / 2015 / 716 vom 18. August 2015 - VD Tribunal cantonal (2015)
EXPULSION DE LOCATAIRE, LOCAL PROFESSIONNEL, COMPENSATION DE CRÉANCES, BAIL À LOYER | 257d al. 1 CO, 257d al. 2 CO, 257d CO